Questioning Assumptions about Race, Social Class and Crime Portrayal: An Analysis of Ten Years of Law and Order - Case, Patricia (International Journal of Criminology and Sociology, 2013)
Social researchers have paid significant interest to the portrayal of non-whites and members of the lower classes in both news broadcasts and the fictional crime drama. They have also explored whether social programming uses educational entertainment to positively sway public opinion or as propaganda to support the status quo. Little has been done recently to determine the representation of intra- versus interracial crime in the crime drama. Also, there is the underlying assumption that may be taken almost a priori by viewers that criminals are more often portrayed as poor and non-white and victims are more often portrayed as whites with more resources. This study utilizes the first ten year of Law and Order, an immensely successful crime drama. It explores both the portrayal of victims and perpetrators by race and social class as well as an examination of how these topics are framed and communicated to the public. Descriptive statistics are used to determine whether the portrayal by race and social class is reflective of crime rates during the decades. A content analysis is used to determine if topics that deal specifically with these factors are designed to educate, maintain the status quo, or perhaps accomplish both goals.